THE USE OF THE SINGING METHOD IN INCREASING THE LEARNING OUTCOMES OF CLASS V IN THEMATIC LEARNING - Khusna, Syifa Wafirotul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2023)
The purpose of this study was to improve student learning outcomes by using the singing method in thematic learning in VA MI Ma'arif NU 1 Cilongok class. This study used a class action research method using the Kurt Lewin model which was carried out in two cycles, each cycle consisting of several stages, namely preparation, action, observation, and reflection. The subjects in this study were 24 students of VA MI Ma'arif NU I Cilongok class, the number of male students. The data source in this study is information about learning outcomes after applying the singing method. The results of this study indicate that the application of the singing method can improve learning outcomes in the form of students' mastery and understanding. This can be proven by cycle I where student learning outcomes have an average of 70.9% which can be categorized as not meeting the assessment standards, while in cycle II student learning outcomes show an average of 81.36% and can be categorized as complete. Changes in behavior shown in the learning process with this singing method are students feeling happy, cheerful, active, and more enthusiastic in learning thematic learning.